Facile synthesis of a highly luminescent carbon dot@silica nanorattle for in vivo bioimaging1. Issue 57 (25th June 2015) - Fu, Changhui; Qiang, Li; Liang, Qinghua; Chen, Xue; Li, Linlin; Liu, Huiyu; Tan, Longfei; Liu, Tianlong; Ren, Xiangling; Meng, Xianwei
<x xml:space="preserve">Abstract</x> Carbon dots embedded in silica nanorattle (CDs@SN) nanocomposites with high luminescence are synthesized and exhibit brighter fluorescence in vitro and in vivo than CDs alone.